Strength and Fatigue Analysis of Double Arc Planetary Gear Transmission System - Youjun Zhang; Taotao Wang; Longgui Zhao (Jixie chuandong)
In order to accurately evaluate the strength and fatigue characteristics of the double arc planetary gear transmission system in actual work，the three-dimensional geometric model of the double-arc planetary gear transmission system is established，by using HyperMesh a high-quality hexahedral mesh is obtained，combining with Ansys a finite element model is established and the transient dynamic analysis is carried out，the change curve of equivalent stress and contact pressure during the movement of the transmission system are obtained. At the same time，the fatigue life analysis is carried out based on the finite element model using Fatigue Tool. The results show that the stress of the transmission system is concentrated on the meshing end surface of the planetary gear and the sun gear during the meshing process. The contact stress changes smoothly，and the entire structure has a small impact. Fatigue damage is concentrated on the meshing position of the planetary gear and the sun gear.